Geospatial Technology as an Evidentiary Instrument in Forestry Crimes in Indonesia - Barus, Firdaus; Zarzani, T. Riza; Mhd. Azhali Siregar (International Conference Epicentrum of Economic Global Framework, 2026)
Deforestation remains an unresolved challenge in Indonesia, where forestry crimes continue to threaten the sustainability of natural resources and the nation's ecological resilience. The enforcement of criminal law in the forestry sector frequently encounters significant evidentiary challenges, particularly in establishing the locus delicti and the spatial extent of illegal activities occurring within forest areas that are difficult to access through conventional field investigations. This study examines the role of geospatial technologies, including Geographic Information Systems (GIS), remote sensing, and satellite imagery, as evidentiary instruments in the adjudication of forestry crime cases in Indonesia. The research employs a normative legal method combined with statutory, conceptual, and case approaches to analyze the Indonesian legal framework governing criminal evidence under the Criminal Procedure Code (KUHAP) and relevant sector-specific regulations. The findings demonstrate that geospatial data may be accommodated within the evidentiary framework as expert testimony, documentary evidence, and judicial indications, as recognized under the KUHAP. Furthermore, the evidentiary value of geospatial information is reinforced by Article 5 of the Electronic Information and Transactions Law (ITE Law), which recognizes electronic documents as legally valid evidence. The study also identifies structural constraints in the investigation of forestry crimes, particularly the prolonged reliance on expert witnesses for the interpretation and verification of geospatial evidence. In response, it proposes a comprehensive normative framework to strengthen the integration of geospatial technology into criminal evidentiary procedures, thereby enhancing legal certainty, investigative efficiency, and the effectiveness of forestry law enforcement in Indonesia.